2022
DOI: 10.1039/d1cs00908g
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic self-transfer hydrogenolysis of lignin with endogenous hydrogen: road to the carbon-neutral future

Abstract: This review describes recently developed self-transfer hydrogenolysis for the lignin depolymerization using itself as a hydrogen donor and proposes a concept of endogenous hydrogen efficiency to assess the utilization rate of endogenous hydrogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(85 citation statements)
references
References 51 publications
1
84
0
Order By: Relevance
“…Moreover, methanol underwent aqueous phase reforming to produce more H 2 , thus accelerating the whole reaction. 23 Again, the Ru 2.6 /NiAl 2 O 4 catalyst exhibited a better demethoxylation performance than that of Ru 1.5 / NiAl 2 O 4 , in which the yield of 4-EP reached 42% after 16 h, while it was only 31% over the Ru 1.5 /NiAl 2 O 4 catalyst (Fig. 4a and b), in agreement with the results in Table 1.…”
Section: Reaction Pathway Studiessupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, methanol underwent aqueous phase reforming to produce more H 2 , thus accelerating the whole reaction. 23 Again, the Ru 2.6 /NiAl 2 O 4 catalyst exhibited a better demethoxylation performance than that of Ru 1.5 / NiAl 2 O 4 , in which the yield of 4-EP reached 42% after 16 h, while it was only 31% over the Ru 1.5 /NiAl 2 O 4 catalyst (Fig. 4a and b), in agreement with the results in Table 1.…”
Section: Reaction Pathway Studiessupporting
confidence: 89%
“…Apart from additional hydrogen, the benzyl-hydroxyl units in the side-chain 22 and methoxyl groups of lignin have also been proven to be hydrogen sources. 23 Previously, our group developed a H 2 -free strategy to obtain 4-alkylphenols via a self-reforming-driven depolymerization and hydrogenolysis of lignin or lignin oils over Pt/NiAl 2 O 4 catalyst. 24 Furthermore, the influence of different metals (Pt, Pd, and Ru) on catalyst performance was studied, and it was found that Ru had the best catalytic activity due to its excellence in dehydrogenation and demethoxylation, a rate-determining step (RDS).…”
Section: Introductionmentioning
confidence: 99%
“…10d), in-depth mechanistic insights announced that the holes oxidized the alcoholic group (C α H-OH) to deliver ketone intermediates and protons, which were reduced by electrons to hydrogen subsequently on the surface of the catalyst. 37,107 The interfacial adsorbed hydrogen could reductively dissociate the C β -O bond in the β-O-4′ ketone intermediate. This reaction mode, generally dubbed self-transfer hydrogenolysis, captures the hydrogen generated by the oxidative dehydrogenation of C α H-OH to further break the C β -O bond.…”
Section: Lignin Depolymerization By Photocatalytic C-o Bond Cleavagementioning
confidence: 99%
“…In this case, cleavage of the sp 3 C-O bond to phenolic products would take preference over cleavage of the ArO-Alkyl sp 2 C-O bond that gives rise to the corresponding deoxygenized aromatics. Moreover, a retro-aldol pathway could be taken for the hydrogenolytic cleavage of the ArO-Alkyl ether moieties [52]. Noteworthy is the hydroxy group attached to the ß-carbon that may enable this transformation (Figure 7, circles).…”
Section: Hydrogenolytic Cleavage Of Aryl Ether Moieties In Lignin Dep...mentioning
confidence: 99%